(untitled) (Research, Society and Development, 2021)
Objective: to analyze in scientific productions the evidence related to the challenges of the multidisciplinary team in the management of health waste in the prevention and control of hospital infection. Method: What are the challenges of the multidisciplinary team in the management of health waste aiming at the prevention and control of hospital infection? Integrative Review of qualitative approach, searching for articles in the databases that make up the Virtual Health Library. Results: 10 articles were included, for the construction of this integrative review and ordered by didactic similarity according to the challenges of the multidisciplinary team. Conclusion: Evidence shows that the multidisciplinary team faces structural and compliance challenges in waste management. However, it is worth mentioning that both permanent education aimed at training employees and managers and the management of appropriate RSS, contribute to infection control, ensuring safety and reducing threats of exposure to human health.